Making Usable Moisturizing Solid Bath Soap Of Tomato Juice (Solanum Lycopersicum L.) - Angelia Fransisca Patriana Siburian; Artha Yuliana Sianipar (TOUR HEALTH JOURNAL, 2022)
Tomato (Solanum lycopersicum L.) is one of the foodstuffs with sufficient antioxidant content, which are lycopene, polyphenols and vitamin C. Antioxidants can protect the human body from repairing damage caused by reactive oxygen and other free radicals. The purpose of this study was to formulate the tomato juice in solid soap form, determined its moisturizing effectiveness, and the quality assessment of solid soap based on Indonesian National Standard. The preparation of solid soap was started from blank formula (F0) and the addition of simplicia in various concentrations of 5% (F1), 10% (F2) and 15% (F3). Physical stability testing of preparations included of irritation test and hedonic on volunteers’ skin, and skin moisture test. Inspection of solid soap quality based on Indonesian National Standard which are pH, foam height, free alkali and free fatty acid. The result of this study is tomato juice could be formulated into solid soap did not irritate volunteers’ skin. Soap containing exfoliant with 15% concentration (F3) moisturize the skin the most, with 40,80% moisture increased. The solid soap also fulfilled the Indonesian National Standard, their pH were 9.61-9.83, stable foam, 0.08% free alkali, and 0,765% free fatty acid. Solid soap preparations containing tomato juice with 15% concentration gave the best effectiveness to moisturize the skin and fullfiled the Indonesian National Standard.